Finding common threads: How patients, physicians and nurses perceive the patient gown - Christy Lucas; Cheryl Dellasega (The Beryl Institute, 2020)
Evidence-based care is standard practice in medicine, but the patient gown has fallen outside the scope of scholarly research. The current gown renders a patient vulnerable, diminishing patients' sense of identity, agency, and dignity with its one-size-fits-none design. The impact on providers is similarly neglected. Our objective was to explore how patients and providers derive meaning from patient gowns. A convenience sample at an academic medical center was interviewed utilizing a standardized framework developed by a medical student and two PhD-prepared researchers with experience in qualitative methods. The study was inductive in nature, seeking to understand perceptions of the patient gown through thematic analysis of transcripts within and across interviews. Participants were ten patients (5 women, 5 men; mean (SD) age = 56.4 (19.1)) years, ten nurses (9 women, 1 man; mean (SD) age = 36.5 (13.4)) years, and ten physicians (6 women, 4 men; mean (SD) age = 48.6 (14.4)) years. Themes within patients' interviews suggest gowns are provider-driven, the design is problematic, gowns reduce self-esteem, and color options would be empowering. Themes within providers' interviews addressed gowns theoretically vs. practically, attire biases, and distress from seeing patients in gowns. Common themes among groups included: negative first impressions of gowns, ideas for improvement, and barriers to change. This is the first study to ascertain how patients and providers perceive patient gowns and offer the opportunity to describe and sketch an "ideal" alternative. The current gown satisfies neither patients nor providers, and flaws must be addressed to improve patient and provider experiences. Experience Framework This article is associated with the Environment & Hospitality lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Environment%20%26%20Hospitality%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.